The silentfight 1 An interpretation ofWestphalen says an uncollected poem by Jorge Eduardo Eielson - Lopez Velarde, Andres (2004)
Silence as a distinctive trait in modern poetry is recognizable in the poeticwork of J.E.E. Through a particular interpretation of one of his uncollectedpoems ("Westphalen says") a general reflection about such aspect is hereundertaken. It will show the way in which silence is omnipresent from theinceptron of the creative act, progresses as an impossible fusion with thesource it carne from, denouncing on the way language's critica! situationby which the poem announces the failure of poetic writing and acontinuous will to get rid of words.